Structural and functional motor cortex asymmetry in unilateral lower limb amputation with phantom limb pain. Issue 10 (October 2020) - Pacheco-Barrios, K.; Pinto, CB.; Saleh Velez, FG.; Duarte, D.; Gunduz, ME.; Simis, M.; Lepesteur Gianlorenco, AC.; Barouh, JL.; Crandell, D.; Guidetti, M.; Battistella, L.; Fregni, F.
Highlights: There is an asymmetrical reorganization of the motor cortex in patients with phantom limb pain. We found disorganized and shifted hand cortical representation in the affected hemisphere. This reorganization is not associated with pain intensity. Abstract: Objective: The role of motor cortex reorganization in the development and maintenance of phantom limb pain (PLP) is still unclear. This study aims to evaluate neurophysiological and structural motor cortex asymmetry in patients with PLP and its relationship with pain intensity. Methods: Cross-sectional analysis of an ongoing randomized-controlled trial. We evaluated the motor cortex asymmetry through two techniques: i) changes in cortical excitability indexed by transcranial magnetic stimulation (motor evoked potential, paired-pulse paradigms and cortical mapping), and ii) voxel-wise grey matter asymmetry analysis by brain magnetic resonance imaging. Results: We included 62 unilateral traumatic lower limb amputees with a mean PLP of 5.9 (SD = 1.79). We found, in the affected hemisphere, an anterior shift of the hand area center of gravity (23 mm, 95% CI 6 to 38, p = 0.005) and a disorganized and widespread representation. Regarding voxel-wise grey matter asymmetry analysis, data from 21 participants show a loss of grey matter volume in the motor area of the affected hemisphere. This asymmetry seems negatively associated with time since amputation. For TMS data, only the ICF ratio is negatively correlated with PLP intensity (r = −0.25, p = 0.04). Conclusion: There is an asymmetrical reorganization of the motor cortex in patients with PLP, characterized by a disorganized, widespread, and shifted hand cortical representation and a loss in grey matter volume in the affected hemisphere. This reorganization seems to reduce across time since amputation. However, it is not associated with pain intensity. Significance: These findings are significant to understand the role of the motor cortex reorganization in patients with PLP, showing that the pain intensity may be related with other neurophysiological factors, not just cortical reorganization.